Political Dimensions of Research by Design. Issue 1 (11th March 2022) - Liekens, Johan; Nilsson, Fredrik; Janssens, Nel
In this overview essay, which also introduces the other contributions to the AJAR Special Collection about the Erasmus+-funded research project on 'Mapping, Reflecting and Developing PhD-by-Design Programs', we as the guest editors venture from a situated position based on our experiences of that collaborative process. From that stance, and as part of the dynamics sprouting from the Mapping/Reflecting/Developing project, we focus here on one specific characteristic of research-by-design – that of the inherently political dimension in positioning such research. It is a dimension which often seems to be ignored or under-articulated within discussions about Research-by-Design projects and PhD-by-Design programs. To counteract that deficiency, the notion of the 'political' is connected in this introductory essay to the realms of architecture, architectural practice, and architectural design research, on multiple levels. For the other essays which make up this Special Collection, this essay presents what we call the 'agonistic table'.